Concepção de um portal das webquests em língua portuguesa : análise de sites existentes e identificação das suas características - Bottentuit Junior, João Batista (2007)
The number of educational sites is growing tremendously, due to the easiness to create and edit web pages. However, many of these sites have ill-structured information, the conditions of reading are not good as well as much of the information quality and update available to the users. Within the scope of the activities to develop a research project, which has as main goal the creation of an educational portal for Portuguese Language WebQuests, sixteen websites within this theme were inventoried and chosen to be analized, in order to compare some aspects related to the usage, the available content and its importance to the users. The analysis of the results led to a first proposal for the above-mentioned educational portal, which we hope can be a space for share and debates between those who believe this is a powerful educational strategy.